From Challenges to Change: A Holistic Framework for Police Reforms in the Rohtak Range - Kumar , Sudhir; Kamaraja, V. (Journal of Neonatal Surgery, 2025)
Police reform in India has long been a multifaceted challenge encompassing legal, administrative, political, and societal dimensions. Despite statutory interventions, including the Haryana Police Act, 2007, the translation of legislative objectives into operational efficiency and community trust remains uneven across regions. This study focuses on the Rohtak Range of Haryana, which comprises Rohtak, Sonipat, Panipat, and Jhajjar districts, a strategically significant area due to its proximity to the National Capital Region, diverse socio-economic profile, and a mix of urban-industrial and agrarian policing demands. The research employs a mixed-methods approach, combining doctrinal analysis, primary field data (interviews, surveys), and secondary crime statistics from 2023-2024 to identify structural, operational, and community-related challenges. Key issues include political interference, resource shortages, skill deficits, delayed case closures, and limited public trust, particularly in districts such as Jhajjar and Sonipat. Based on these insights, a five-pillar holistic reform framework is proposed, integrating structural safeguards, technological enhancement, human capital development, community partnership, and transparent governance. A pilot intervention model was designed to evaluate pre- and post-intervention outcomes using key performance indicators such as response time, case clearance rates, citizen trust, and training completion. Analysis demonstrates measurable improvements across all indicators, with Panipat showing the highest operational efficiency and Jhajjar exhibiting substantial but ongoing gaps. Bar chart visualizations and descriptive statistics confirm the efficacy of targeted reforms in improving police performance and community confidence. The study concludes that region-specific, evidence-driven reforms are critical for translating statutory mandates into actionable outcomes. Policymakers are encouraged to prioritize targeted interventions, continuous monitoring, and participatory community engagement to ensure sustainable improvements. The Rohtak Range pilot offers a replicable model for broader application across Haryana and other Indian states seeking accountable, responsive, and modern policing practices.